1996
DOI: 10.2135/cropsci1996.0011183x003600020025x
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Dissipation under Golf Course Fairway Conditions

Abstract: The degradation and vertical movement of pendimethalin, chlorpyrifos, isazofos, and metalaxyl were monitored in Kentucky bluegrass (Poapratensis L.) turf managed as a golf course fairway. Intact turf‐soil cores from Mead, NE, on a Sharpsburg soil (fine montmorillonitic, mesic Typic Argiudoll) and Gilbert, IA, on a Nicollet loam (fine‐loamy, mixed, mesic Aqnic Hapludoll) planted to Kentucky bluegrass were periodically removed to 60‐cm depth through 113 d after pesticide application. Cores were sectioned into ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 0 publications
6
47
0
Order By: Relevance
“…Field studies of pendimethalin have indicated very little leaching through soil columns (21). This lack of movement, coupled with previous reports of higher dissipation rates of pendimethalin on golf course thatch (15), may explain why detectable water contamination was not present on the golf course. However, if contamination of the water did occur, pendimethalin is likely to partition quickly into the sediment, which was not tested.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Field studies of pendimethalin have indicated very little leaching through soil columns (21). This lack of movement, coupled with previous reports of higher dissipation rates of pendimethalin on golf course thatch (15), may explain why detectable water contamination was not present on the golf course. However, if contamination of the water did occur, pendimethalin is likely to partition quickly into the sediment, which was not tested.…”
Section: Discussionmentioning
confidence: 88%
“…For instance, pendimethalin has been reported to have dissipation half-lives of 37 days in onion fields (13), 47 days in agronomic soil (14), and 12 days in thatch on a golf course (15). Other laboratory studies have reported pendimethalin half-lives as long as 98 days at 30°C and 407 days at 10°C (16).…”
Section: Discussionmentioning
confidence: 99%
“…The increased sorption correlates to a lower potential for fungicides in turf to migrate off site. Horst et al (1996) evaluated four pesticides for their mobility in a Kentucky bluegrass fairway.…”
Section: Fungicide Mobilitymentioning
confidence: 99%
“…The third factor in determining fungicide performance is persistence in the environment (Latin, 2011 Horst et al (1996) reported the half-lives of metalaxyl, pendimethalin, chlorpyrifos, and isazofos in a Kentucky bluegrass fairway to be 16, 12, 10, and 7 days, respectively. These values are lower than half-lives of these pesticides in agricultural soils.…”
Section: Fungicide Persistence In Verdure and Thatchmentioning
confidence: 99%
See 1 more Smart Citation